The effect of in vitro gastrointestinal digestion on the phenolic profiles, bioactivities and bioaccessibility of Rhodiola. Issue 10 (9th May 2022) - Zhang, Sheng; Deng, Na; Zheng, Bisheng; Li, Tong; Liu, Rui Hai
Abstract : Present study unravels the underlying mechanism of Rhodiola colon digesta on the enhancement of cell bioaccessibility: down-regulation of ABCF2 protein. Abstract : Changes in the phenolic profiles and antioxidant and antiproliferative activities of Rhodiola after simulated in vitro digestion were first assessed in this study. Furthermore, permeability and uptake assays as well as RT-qPCR and western blot analyses were performed in order to explore the bioaccessibility of the digesta and its underlying mechanism. The results reveal that in vitro gastrointestinal digestion significantly reduced the total phenolics and total flavonoids as well as the extracellular, cellular antioxidant and antiproliferative activities of Rhodiola, in which the colon digesta had the largest reduction. However, in vitro digestion augmented the cellular uptake rates of Rhodiola phenolics with higher permeability coefficients. The colon digesta (GA-Dig) exhibited the highest uptake of gallic acid (GA, the main compound) instead of GA in its pure form, indicating the synergistic effects of GA and other phenolics in Rhodiola . In-depth mechanistic studies suggest that the fabulous uptake rates and permeability coefficients of the colon digesta were triggered by the down-regulation of the expression levels of ABCF2 mRNA and protein. These findings indicate that simulated gastrointestinal digestion could promote the bioaccessibility and bioactivities of phenolics in Rhodiola .